Cointegration analysis of broiler meat and broiler feed prices in Turkey - Arıkan, Mehmet Saltuk; Çevrımlı, Mustafa Bahadır; Akın, Ahmet Cumhur; Mat, Burak; Tekindal, Mustafa Agah (My University, 2019)
Aim: The high share of feed costs among the costs of inputs used in broiler breeding plays a significant role in the formation of broiler meat price. As the production of raw materials used in the broiler feed industry is not sufficient to meet the demand in the domestic market, the demand is met by importation. As such, the fluctuations in the exchange rates are reflected in the price of the final product. The aim of this study is to analyze the relationships between the variables of broiler meat and broiler feed price series.Materials and Methods: In Turkey, the relations between the variables related to the price series of broiler meat and broiler feed in TL and in USD between 2006 and 2018 were determined by johansen cointegration analysis technique.Results: The results of the analysis indicate that the broiler feed and broiler meat prices in Turkey are cointegrated in the short-term and follow each other's pattern. It was found that the change in the prices of feed had an effect on the TRY-denominated prices of poultry meat in two months and USD-denominated prices of poultry meat in onemonth.Conclusion: Consequently, broiler meat prices should be set taking into account the costs of inputs in the short-term. However, since the fluctuations in the USD exchange rate affect the input prices immediately, an effective price mechanism for broiler prices cannot be developed.
Keywords: Beslenme ve Diyetetik; Tarımsal Ekonomi ve Politika; Gıda Bilimi ve Teknolojisi; İktisat